2011
DOI: 10.1016/j.dsr.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The inner ear and its coupling to the swim bladder in the deep-sea fish Antimora rostrata (Teleostei: Moridae)

Abstract: The inner ear structure of Antimora rostrata and its coupling to the swim bladder were analyzed and compared with the inner ears of several shallow-water species that also have similar coupling. The inner ear of Antimora has a long saccular otolith and sensory epithelium as compared to many other fishes. Some parts of the membranous labyrinth are thick and rigid, while other parts are thinner but attached tightly to the bony capsule. The partially rigid membranous labyrinth, along with its intimate connection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
(78 reference statements)
0
32
0
Order By: Relevance
“…In other species, attachment of one or several otolith end organs to the skull is associated with the presence of accessory hearing structures as found in the notopterid Chitala chitala, the morid Antimora rostrata, or the cichlid Etroplus maculatus Deng et al, 2011;SchulzMirbach et al, 2013). This coupling of an otolith end organ to the bone may play a role for effective sound transmission to the ears via the specialized swim or gas bladder (see discussion in Deng et al, 2011).…”
Section: Diversity In Gross Inner Ear Morphologymentioning
confidence: 99%
See 3 more Smart Citations
“…In other species, attachment of one or several otolith end organs to the skull is associated with the presence of accessory hearing structures as found in the notopterid Chitala chitala, the morid Antimora rostrata, or the cichlid Etroplus maculatus Deng et al, 2011;SchulzMirbach et al, 2013). This coupling of an otolith end organ to the bone may play a role for effective sound transmission to the ears via the specialized swim or gas bladder (see discussion in Deng et al, 2011).…”
Section: Diversity In Gross Inner Ear Morphologymentioning
confidence: 99%
“…Certain teleosts such as poeciliids show rather "free" ears with encapsulation limited to the semicircular canals (Schulz-Mirbach et al, 2011), whereas the non-teleost actinopterygian Amia calva (Popper and Northcutt, 1983) or elasmobranchs display almost full encapsulation of the ears (Maisey, 2001). In other species, attachment of one or several otolith end organs to the skull is associated with the presence of accessory hearing structures as found in the notopterid Chitala chitala, the morid Antimora rostrata, or the cichlid Etroplus maculatus Deng et al, 2011;SchulzMirbach et al, 2013). This coupling of an otolith end organ to the bone may play a role for effective sound transmission to the ears via the specialized swim or gas bladder (see discussion in Deng et al, 2011).…”
Section: Diversity In Gross Inner Ear Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Fishes with large otoliths produce sounds and show highly developed intraspecific acoustic communication (Luczkovich et al 1999, Holt 2002. These characteristics enable them to live in coastal and deep environments where visual and light communications are less important (Deng et al 2011(Deng et al , 2013. Moreover, it has been reported that females can use the auditory sense to detect and locate vocalizing males during the breeding season and can change their hearing sensitivity depending on their reproductive status (e.g.…”
Section: Introductionmentioning
confidence: 99%